Consumer Behavior in the Digital Age: An Analysis of Changes in Consumption Patterns from a Behavioral Economics Perspective - Suharyanto Suharyanto (PT. Hafasy Dwi Nawasena, 2026)
This study examines changes in consumer behavior in the digital age through a behavioral economics lens, focusing on the cognitive biases, heuristics, and digital nudges that shape consumption patterns in online environments. The rapid expansion of e-commerce and social media platforms has fundamentally altered how individuals make purchasing decisions, introducing unprecedented complexities into consumer psychology. Employing a systematic literature review methodology, this research synthesizes findings from 20 peer-reviewed journal articles published between 2022 and 2025. The analysis reveals that digital environments strategically exploit loss aversion, anchoring bias, herding behavior, and the scarcity effect to stimulate impulsive purchasing and increase transaction volumes. Personalized algorithmic recommendations, social proof mechanisms, and digital payment frictionlessness collectively reduce cognitive resistance and amplify impulse buying tendencies. The study further demonstrates that Generation Z consumers exhibit heightened susceptibility to social media-driven behavioral nudges relative to older demographic cohorts. These findings contribute to the emerging literature on behavioral economics in digital markets by providing an integrated framework that connects specific platform design features with documented cognitive biases. This study concludes that understanding behavioral economic mechanisms in digital consumption contexts is essential for developing effective consumer protection policies and for designing ethically responsible digital marketing strategies.